Pengembangan Computer Based Testing Menggunakan Aplikasi Kahoot! Untuk Evaluasi Pembelajaran - M. Yakub Iskandar; Siti Aisyah; Novrianti Novrianti (STKIP Pesisir Selatan, 2024)
The problem with evaluating learning outcomes using paper-based tests is that the scoring calculation process takes a long time. So, the test results cannot be known directly. The implementation of learning outcomes evaluation in learning evaluation courses so far still uses paper-based tests, so students have to wait to find out the test results. This research and development apply the ADDIE model which is carried out in five stages. The instruments used in this research were tests and student response questionnaires regarding the use of the